The Convergence of Food Expenditures in the European Union Countries – a Spatio‑Temporal Approach - Jankiewicz, Mateusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">The paper presents the analysis of the convergence of household final consumption expenditures on food in the European Union countries in the period of 1999–2015, considering spatial and spatio<span style="line-height: 115%; font-family: 'MS Gothic'; font-size: 11pt; mso-bidi-font-family: 'MS Gothic'; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">‑<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">temporal tendencies and dependencies. The aim of this research is to verify whether space significantly influences the convergence of the considered process. The subject of the investigation is the share of household final consumption expenditures on food in total final consumption expenditures of European countries. Spatial and spatio<span style="line-height: 115%; font-family: 'MS Gothic'; font-size: 11pt; mso-bidi-font-family: 'MS Gothic'; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">‑<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">temporal tendencies and dependencies are surveyed using the conception of spatial and spatio<span style="line-height: 115%; font-family: 'MS Gothic'; font-size: 11pt; mso-bidi-font-family: 'MS Gothic'; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">‑<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">temporal trends and spatial autocorrelation. The convergence of the process is investigated with the use of β<span style="line-height: 115%; font-family: 'MS Gothic'; font-size: 11pt; mso-bidi-font-family: 'MS Gothic'; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">‑<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">convergence models for panel data (also in the spatial terms). Absolute and conditional convergence approaches are applied. For the conditional approach, the models are expanded to incorporate the influence of additional determinants, including space, disposable income and the level of food prices.